Identifying and assessing the factors that affect profitability in contract growing in the cavendish banana industry the case of DARBCO, AMSKARBEMCO, and DARBMUPCO - Antepuesto, Chino Luis M.; Ellson, Adela G.
There is the opportunity for economic growth and development from increasing international trade. On the other hand there is the risk of increased marginalization if small farmers are not integrated into the global supply chain. Contract farming, an agreement between a buyer and grower/s for the production and supply of agri-products, may serve as the linkage between small farmers and the world economy. This study is on contract farming in the export-banana industry, the Philippines' largest fruit industry in terms of volume exported and value. It seeks to find out whether contract farming is an effective marketing and production scheme by identifying and assessing factors that contribute to its success in terms of profitability. Primary data were gathered from 135 respondents belonging to AMSKARBEMCO, DARBMUPCO, and DARBCO. These cooperatives are Agrarian Reform Beneficiaries (ARBs) and are members of FARMCOOP, a federation of farmer cooperatives. Futhermore, secondary data coming from various government agencies and from non-government were gathered. Contracts between the buyer and the three cooperatives were analyzed. In order to identify factors that affected the ARBs' average income, the OLS regression analysis was used. Results showed that farmers' farm size and household size had an affect on average income. Futhermore, the survey revealed that there are other factors that affect average income and these are: FARMCOOP membership, Buyer assistance, Cooperative assistance, and ARBs' punctuality in performing his/her tasks. In assessing each of the cooperatives' profitability, the investment analysis was used. Using reconstructed cash flow statements, the following discount rates were computed: Net Present Value, Benefit -Cost Ratio, and Internal Rate of Return. Results for the investment analysis showed that the three cooperatives' operations are expected to increase the ARBs' income and thus, production and marketing agreements should be continued.
Keywords: AMS Kapalong Agrarian Reform Beneficiaries Multi-purpose Cooperative; Diamond Farms Agrarian Reform Beneficiaries Multi-purpose Cooperative; Dapco Agrarian Reform Beneficiaries Cooperative; Banana trade -- Davao region(Philippines) -- Agriculture cooperatives; Banana trade -- Davao region(Philippines) -- Agriculture cooperatives -- Profits; Cavendish banana trade -- Davao region(Philippines) -- Agriculture cooperatives